2016
DOI: 10.1016/j.mehy.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Possible role of Epoxyeicosatrienoic acid in prevention of oxidative stress mediated neuroinflammation in Parkinson disorders

Abstract: Parkinson’s disease (PD) is a multifactorial neurodegenerative disease involving oxidative stress, neuroinflammation and apoptosis. Epoxyeicosatrienoic acids (EETs) are arachidonic acid metabolites and they play a role in cytoprotection by modulating various cell signaling pathways. This cytoprotective role of EETs are well established in cerebral stroke, cardiac failure, and hypertension, and it is due to their ability to attenuate oxidative stress, endoplasmic reticulum stress, inflammation, caspase activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 69 publications
(69 reference statements)
0
17
0
Order By: Relevance
“…Furthermore 14,15 EET administration protected dopaminergic neurons in mice treated with MPTP. Thus, because of the role neuroinflammation and mitochondrial dysfunction play in PD and the efficacy in preclinical models, it is hypothesized that sEH inhibition may have potential benefit in this condition in humans (Lakkappa, et al, 2016). …”
Section: Seh As a Target For Neurodegenerative Diseasesmentioning
confidence: 99%
“…Furthermore 14,15 EET administration protected dopaminergic neurons in mice treated with MPTP. Thus, because of the role neuroinflammation and mitochondrial dysfunction play in PD and the efficacy in preclinical models, it is hypothesized that sEH inhibition may have potential benefit in this condition in humans (Lakkappa, et al, 2016). …”
Section: Seh As a Target For Neurodegenerative Diseasesmentioning
confidence: 99%
“…To sum up, the previously published results suggested that sEH inhibitors or deletion might be able to protect DA neurons from death. Thus, giving the role that neuroinflammation, OS, and mitochondrial dysfunction play in PD and the efficacy of inhibiting the activity of sEH in preclinical models, sEH is a putative new pharmacological target for the treatment of PD and other α-syn-related pathologies such as Lewis body disease (LBD) [142] (Figures 2 and 3).…”
Section: Soluble Epoxide Hydrolase In Parkinson's Diseasementioning
confidence: 99%
“…Cytochrome P450 3A4 (CYP3A4) expression promotes STAT3-mediated breast cancer cell growth via 14,15-EET [259]. EET analogs and sEH inhibitors are thought to have application in multiple diseases [260], such as Parkinson's [261], renal interstitial fibrosis in obstructive nephropathy [258], marrow or cord blood transplantation [262], inflammatory bowel disease-associated cancer [263], and other cancers [264,265].…”
Section: Epoxyeicosatrienoic Acids (Eets)mentioning
confidence: 99%